2009
DOI: 10.1002/pros.20985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the phytotherapeutic agent Eviprostat® on 17β‐estradiol‐induced nonbacterial inflammation in the rat prostate

Abstract: Eviprostat, which has effective antioxidant and anti-inflammatory activities in the prostate, may be useful for the clinical treatment of chronic prostatitis. These activities of Eviprostat may also contribute to the amelioration of prostate inflammation in BPH patients. Prostate 69: 1404-1410, 2009. (c) 2009 Wiley-Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 22 publications
4
26
2
Order By: Relevance
“…The daily dose of 36 mg/kg Eviprostat produced a downregulation of bladder pro‐inflammatory cytokines, as well as a reduction in oxidative‐stress markers in both AI rats (in the present study) and BOO rats 15 . We have reported that Eviprostat ameliorates carrageenin‐induced paw edema, 14 and reduces oxidative stress and inflammation in the prostate 26,27 . In a clinical study, 18 patients who received daily oral Eviprostat for 4 weeks showed considerably lower urinary oxidative stress marker levels than before treatment.…”
Section: Discussionsupporting
confidence: 56%
“…The daily dose of 36 mg/kg Eviprostat produced a downregulation of bladder pro‐inflammatory cytokines, as well as a reduction in oxidative‐stress markers in both AI rats (in the present study) and BOO rats 15 . We have reported that Eviprostat ameliorates carrageenin‐induced paw edema, 14 and reduces oxidative stress and inflammation in the prostate 26,27 . In a clinical study, 18 patients who received daily oral Eviprostat for 4 weeks showed considerably lower urinary oxidative stress marker levels than before treatment.…”
Section: Discussionsupporting
confidence: 56%
“…Eviprostat is a phytotherapeutic agent commonly used to treat prostatic hypertrophy in Japan [13][14][15]. An experiment using nonbacterial prostatitis model suggested that Evoprostat is potentially effective for the treatment of CP/CPPS.…”
Section: Discussionmentioning
confidence: 99%
“…Oka et al administered Eviprostat treatment in a rat model of nonbacterial prostatitis and reported that oxidative stress and proinflammatory cytokines in the enlarged prostate were considerably suppressed, and that Eviprostat may be useful in the clinical treatment of CP/ CPPS [13][14][15]. Here we conducted a randomized prospective study to determine the effectiveness and safety of Eviprostat to treat CP/CPPS in comparison with pollen extract.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations